Vlastnosti portlandských cementů s ohledem na ekonomickou a ekologickou efektivitu výroby - Walter, Martin (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Diplomová práce pojednává o návrhu složení a postupu výpalu belitického slínku. Dále se zabývá shrnutím poznatků o chemii a technologii výroby portlandských cementů s ohledem na ekologii a jeho ekonomičnost.

Diploma thesis discusses about design composition and firing process modification of belite clinker. It also deals with the summary of knowledge about chemistry and production technology of portland cements with respect to its ecology and economy.
Properties of Portland cements with regard to the economic and ecological efficiency of production
Keywords: Cement; slínek; belit; belitický cement; portlandský cement; emise oxidu uhličitého.; Cement; clinker; belite; belite cement; portland cement; carbon dioxide emissions.